The recent state of cryopreservation techniques for ex-situ gene conservation and breeding purposes in small ruminants: A review - Mujitaba, Malam Abulbashar; Vass, Nóra; Bodó, Szilárd (Acta Agraria Debreceniensis, 2020)
The viewpoint of the recent cryopreservation techniques (CT) suggests the use of a reduced volume of cryopreservation solution, high concentration of cryoprotectants and ultra-rapid cooling and warming rates help to reduce cryo-injury and maximize the viability of the preserved animal genetic resources (AnGR). The CT had now become widely accepted as one of the best methods of choice for the ex-situ conservation of AnGR due to its high success rate recorded and no-invasive nature as compared to the conventional slow rate freezing (CSRF). Rapid advances and wide acceptability of the use of assisted reproductive technologies (ART’s) particularly artificial insemination (AI) in animal breeding had resulted in a greater loss of a large number of good quality genes in virtually almost all the native breeds of animals across the globe. Small ruminant (SR) animals are not an exception in such present predicaments situation of erosion and dilution of the valuable AnGR among the native breeds. As a result of this, 148 and 16 breeds of sheep and goats respectively have already become extinct in Europe and the Caucasus. In view of the aforementioned situation, the present review aimed at exploring some of the current states of development, roles played and potentials of CT in the conservation of SR genes and genome for the immediate and future breeding purposes for sustainable development. It basically covers; animal genetic resource, the need to conserve AnGR, tools for ex situ in vitro conservation of AnGR and recent developments in breeding and cryopreservation of SR AnGR.Cryopreservation is playing a pivotal role in ex-situ gene conservation of AnGR. Decline in genetic diversity among SR breed population was high in Europe and the Caucasus. There is therefore, need for improvent on current stringent measures on conservation of AnGR in this region of the world.